Pendidikan Agama Kristen sebagai Sarana Pembentukan Discernment Rohani: Eksegesis 1 Yohanes 4:1 - Fersal Kinova Rivaldo; Soleman Tinglioy; Robet Matias Laumakan (KARDIA: Jurnal Teologi dan Pendidikan Kristiani, 2026)
Abstract: This study aims to analyse the role of Christian Religious Education (CRE) as a means for forming spiritual discernment based on an exegetical study of 1 John 4:1. The findings indicate that the command dokimazete ta pneumata (“test the spirits”) is a collective imperative that demands active and continuous engagement from the entire community of believers. Spiritual discernment in Scripture is understood as a Spirit-enabled capacity to evaluate teachings, spiritual experiences, and life decisions based on sound Christological confession and ethical fruit consistent with the Gospel. The study further reveals that spiritual discernment develops through the integration of wisdom, faith, and perseverance as complementary elements of spiritual formation. Pedagogically, CRE makes a strategic contribution by strengthening exegetically grounded theological understanding, cultivating mature and critical faith attitudes, and fostering sustained spiritual reflection. Therefore, CRE functions not merely as the transmission of religious knowledge but as a holistic faith formation process that nurtures believers’ spiritual sensitivity. Abstrak: Penelitian ini bertujuan menganalisis peran Pendidikan Agama Kristen (PAK) sebagai sarana pembentukan discernment rohani berdasarkan eksegesis 1 Yohanes 4:1. Hasil penelitian menunjukkan bahwa perintah “δοκιμάζετε τὰ πνεύματα” (ujilah roh-roh) merupakan imperatif kolektif yang menuntut tindakan aktif dan berkelanjutan dari seluruh komunitas orang percaya. Discernment rohani dalam Kitab Suci dipahami sebagai kemampuan yang bersumber dari Roh Kudus untuk menilai ajaran, pengalaman rohani, dan keputusan hidup berdasarkan pengakuan Kristologis yang benar serta buah kehidupan yang selaras dengan Injil. Penelitian ini juga menemukan bahwa discernment rohani bertumbuh melalui integrasi hikmat, iman, dan ketekunan sebagai unsur formasi spiritual yang saling melengkapi. Dalam kerangka pedagogis, PAK memiliki kontribusi strategis melalui penguatan pemahaman teologis berbasis eksegesis, pembentukan sikap iman yang kritis dan dewasa, serta pembiasaan refleksi rohani yang berkelanjutan. Dengan demikian, PAK berfungsi sebagai proses formasi iman yang holistik untuk membangun kepekaan rohani orang percaya